The effectiveness of rural community health workers in improving health outcomes during the COVID-19 pandemic: a systematic review - Neema Kaseje; Meghna Ranganathan; Monica Magadi; Kevin Oria; Andy Haines (Global Health Action)
Background Rural community health workers [CHWs] play a critical role in improving health outcomes during non-pandemic times, but evidence on their effectiveness during the COVID-19 pandemic is limited. There is a need to focus on rural CHWs and rural health systems as they have limited material and human resources rendering them more vulnerable than urban health systems to severe disruptions during pandemics. Objectives This systematic review aims to describe and appraise the current evidence on the effectiveness of rural CHWs in improving access to health services and health outcomes during the COVID-19 pandemic in low-and middle-income countries [LMICs]. Methods We searched electronic databases for articles published from 2020 to 2023 describing rural CHW interventions during the COVID-19 pandemic in LMICs. We extracted data on study characteristics, interventions, outcome measures, and main results. We conducted a narrative synthesis of key results. Results Fifteen studies from 10 countries met our inclusion criteria. Most of the studies were from Asia [10 of 15 studies]. Study designs varied and included descriptive and analytical studies. The evidence suggested that rural CHW interventions led to increased household access to health services and may be effective in improving COVID-19 and non-COVID-19 health outcomes. Overall, however, the quality of evidence was poor due to methodological limitations; 14 of 15 studies had a high risk of bias. Conclusion Rural CHWs may have improved access to health services and health outcomes during the COVID-19 pandemic in LMICs but more rigorous studies are needed during future pandemics to evaluate their effectiveness in improving health outcomes in different settings and to assess appropriate support required to ensure their impact at scale.